Acute prurigo simplex in humans caused by pigeon lice - Stolf, Hamilton Ometto; Espósito, Ana Cláudia Cavalcante [UNESP]; Reis, Rejane D’Ávila; Haddad, Vidal [UNESP] (FapUNIFESP (SciELO), 2018)
Pigeon lice are insects that feed on feathers of these birds; their life cycle includes egg, nymph and adult and they may cause dermatoses in humans. Four persons of the same family, living in an urban area, presented with widespread intensely pruritic erythematous papules. A great number of lice were seen in their house, which moved from a nest of pigeons located on the condenser of the air-conditioning to the dormitory of one of the patients. Even in urban environments, dermatitis caused by parasites of birds is a possibility in cases of acute prurigo simplex. Pigeon lice are possible etiological agents of this kind of skin eruption, although they are often neglected, even by dermatologists.
Keywords: Anoplura; Ectoparasitic infestations; Lice infestations; Mite infestations; Mites; Phthiraptera; Prurigo